Productivity-enhancing labour reallocation in Australia - Dan Andrews; David Hansell (The Australian Government, The Treasury, 2019)
International evidence suggests that aggregate productivity growth is driven by the within-industry reallocation of inputs away from less productive firms and towards more productive firms, but little is known about this process in Australia. Accordingly, this paper exploits firm-level data to explore the nature of productivity-enhancing labour reallocation in Australia over the period 2002-2016. We first show that more productive firms on average account for a higher share of industry employment, particularly in sectors more exposed to competitive pressure via trade, and that this contributes positively to the aggregate level of productivity in Australia. Moreover, we show that the Australian economy is more successful at reallocating resources to high productivity firms than many other OECD countries, which is consistent with Australia's relatively sound structural policy environment that promotes economic flexibility. We then explore the extent to which labour is moving in the right direction over time. While high-productivity firms are more likely to expand and low-productivity firms are more likely to contract (or exit), the extent to which this is true has diminished over time. Counterfactual analysis shows that the weakening responsiveness of employment growth to firm productivity this decade is a significant drag on aggregate labour productivity growth, which motivates further analysis of structural policies that affect competition and labour mobility.
Keywords: C23; C55; D22; D30; E23; E24; 330; productivity; dispersion; firm-level; BLADE